Peran Kuliah Kerja Nyata (KKN) dalam Sosialisasi dan Implementasi Teknologi Budidaya Ikan Lele Skala Mikro - Eka Wahyu Ningsih; Yusuf Iskandar; Bunga Indah; Citra Laksmi Prasita; Fifi Hidayatul Ilmia; Aprilia Dwi Ruslantini; Maria Sri Vandriyani (Jurnal Pengabdian Masyarakat Waradin, 2025)
Community Service Program (KKN) is one of the community engagement activities that involves students in contributing directly to community empowerment and sustainable development. The KKN program implemented in Candinegoro Village focused on the socialisation and application of micro-scale catfish farming technology as an effort to support food security through city farming initiatives. This study employed a qualitative descriptive approach with a participatory method, in which students acted as facilitators, trainers, and companions for the community throughout the program. The activities included socialisation, technical training, and mentoring related to catfish cultivation, covering aspects such as the selection of superior seeds, effective feed management, water quality monitoring, and the innovative use of plastic drums as alternative farming media. The results showed a significant increase in community knowledge and practical skills in fish farming, alongside a growing interest in developing post-harvest innovations such as processed catfish products to enhance added value and income. Furthermore, the program strengthened community awareness of the importance of sustainable urban farming practices as a solution to limited land availability. Overall, this program not only improved community capacity in aquaculture but also promoted local food self-sufficiency and economic resilience, in line with the government’s Asta Cita agenda to strengthen national food security and community empowerment.